Analisa pengaruh jarak cutting torch terhadap permukaan berputar pada mesin pemotong kontur sambungan pipa - Amnur Akhyan; Hadi Salam (Universitas Muhammadiyah Metro, 2022)
Currently steel pipes are needed, especially in construction work. Construction with pipe materials cannot be separated from the process of joining and cutting. The cutting process for large pipes always uses a thermal cutting process. This study aims to determine how much influence the cutting distance has on the cutting results on a pipe that rotates at a constant 0.8 rpm following the shape of the corner joint contour. To achieve the objectives of this study, a pipe cutting tool with a diameter of 4 to 6 inches is needed with the thermal cutting method using the Oxy Acetylene Cutting (OAC) processÂ This research data was obtained by cutting the 4inch pipe schedule 10s, schedule 20s and schedule 40s in a rotating condition and the cutting torch moves back and forth. The pipe rotates at 0.8 rpm using an AC motor transmitted using a gearbox connected to the wheel as a holder where the pipe rotates. The results of the cutting are in the form of a pipe connection contour with an angle of 900 and 600. As the independent variable in this study was set the cutting distance is 5mm, 7mm and 10 mm, while the fixed variables are determined by cutting speed 280 mm/minute, acetylene gas pressure 3.5 kg/cm2 and oxygen 17.5 kg/cm2. In order to get effective results, preheat the surface of the pipe with a gas fuel mixture until it reaches the melting temperature of the pipe as the main ingredient. The cutting results that meet the entire path of the pipe can be cut completely and through and there is very little splash or melt dirt during the cutting process. After cutting, the best results are obtained at a cutting distance of 5 mm both on schedule 10s, schedule 20s and schedule 40s.